Exposure to Artificial Light at Night and the Consequences for Flora, Fauna, and Ecosystems - Falcón, Jack; Torriglia, Alicia; Attia, Dina; Viénot, Françoise; Gronfier, Claude; Behar-Cohen, Francine; Martinsons, Christophe; Hicks, David (Frontiers in Neuroscience, 2020)
The present review draws together wide-ranging studies performed over the last decades that catalogue the effects of artificial-light-at-night (ALAN) upon living species and their environment. We provide an overview of the tremendous variety of light-detection strategies which have evolved in living organisms - unicellular, plants and animals, covering chloroplasts (plants), and the plethora of ocular and extra-ocular organs (animals). We describe the visual pigments which permit photo-detection, paying attention to their spectral characteristics, which extend from the ultraviolet into infrared. We discuss how organisms use light information in a way crucial for their development, growth and survival: phototropism, phototaxis, photoperiodism, and synchronization of circadian clocks. These aspects are treated in depth, as their perturbation underlies much of the disruptive effects of ALAN. The review goes into detail on circadian networks in living organisms, since these fundamental features are of critical importance in regulating the interface between environment and body. Especially, hormonal synthesis and secretion are often under circadian and circannual control, hence perturbation of the clock leads to hormonal imbalance. The review addresses how the ubiquitous introduction of light-emitting diode technology may exacerbate, or in some cases reduce, the generalized ever-increasing light pollution. Numerous examples are given of how widespread exposure to ALAN is perturbing many aspects of plant and animal behaviour and survival: foraging, orientation, migration, seasonal reproduction, colonization and more. We examine the potential problems at the level of individual species and populations and extend the debate to the consequences for ecosystems. We stress, through a few examples, the synergistic harmful effects resulting from the impacts of ALAN combined with other anthropogenic pressures, which often impact the neuroendocrine loops in vertebrates. The article concludes by debating how these anthropogenic changes could be mitigated by more reasonable use of available technology – for example by restricting illumination to more essential areas and hours, directing lighting to avoid wasteful radiation and selecting spectral emissions, to reduce impact on circadian clocks. We end by discussing how society should take into account the potentially major consequences that ALAN has on the natural world and the repercussions for ongoing human health and welfare.